Pemikiran Nurcholish Madjid Tentang Moderasi Beragama: Relevansinya Dalam Menghadapi Radikalisme di Indonesia - Siti Nurhamidah Auliani; Afifah Nur Zakiah; Filjah Hasyati; Muhammad Nathan; Abdul Fadhil (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
In the midst of the phenomenon of radicalism that threatens diversity and tolerance in Indonesia, Nurcholis Madjid's thoughts on religious moderation have become a concern again. Taking into account the history and development of Islamic thought in Indonesia, this article investigates the idea of religious moderation in Madjid. To determine whether Madjid's ideas are relevant to radicalism, a thorough examination of the theological, philosophical, and sociological foundations of his thinking will be carried out. This article will also look at how the idea of religious moderation can be applied to various aspects of life, as well as the challenges and opportunities faced in an effort to create a more moderate Indonesian society. Radicalism now threatens the life of the nation and state. In this case, the perspective of religious moderation Nurcholis Madjid offers a profitable option. In this article, the concept of religious moderation in Madjid will be discussed thoroughly, with a special emphasis on practical solutions.